Polymeric cobalt(ii) thiolato complexes – syntheses, structures and properties of 1∞[Co(SMes)2] and 1∞[Co(SPh)2NH3]. Issue 43 (10th October 2016) - Eichhöfer, Andreas; Buth, Gernot
Abstract : Structural and magnetic characterization of the first examples of polymeric cobalt chalcogenolato complexes namely 1∞[Co(SMes)2 ] and 1∞[Co(SPh)2 NH3 ]. Abstract : Reactions of [Co(N(SiMe3 )2 )2 thf] with 2.1 equiv. of MesSH (Mes = C6 H2 -2, 4, 6-(CH3 )3 ) yield dark brown crystals of the one dimensional chain compound 1∞[Co(SMes)2 ]. In contrast reactions of [Co(N(SiMe3 )2 )2 thf] with 2.1 equiv. of PhSH result in the formation of a dark brown almost X-ray amorphous powder of 'Co(SPh)2 '. Addition of aliquots of CH3 OH to the latter reaction resulted in the almost quantitative formation of crystalline ammonia thiolato complexes either [Co(SPh)2 (NH3 )2 ] or 1∞[Co(SPh)2 NH3 ]. Single crystal XRD reveals that 1∞[Co(SPh)2 NH3 ] forms one-dimensional chains in the crystal via μ2 -SPh bridges whereas [Co(SPh)2 (NH3 )2 ] consists at a first glance of isolated distorted tetrahedral units. Magnetic measurements suggest strong antiferromagnetic coupling for the two chain compounds 1∞[Co(SMes)2 ] ( J = −38.6 cm −1 ) and 1∞[Co(SPh)2 NH3 ] ( J = −27.1 cm −1 ). Interestingly, also the temperature dependence of the susceptibility of tetrahedral [Co(SPh)2 (NH3 )2 ] shows an antiferromagnetic transition at around 6 K. UV-Vis-NIR spectra display d–d bands in the NIR region between 500 and 2250 nm. Thermal gravimetric analysis of [Co(SPh)2 (NH3 )2 ] and 1∞[Co(SPh)2 NH3 ] reveals two well separated cleavage processes for NH3 and SPh2 upon heating accompanied by the stepwise formation of 'Co(SPh)2 ' and cobalt sulfide.